Microplastic occurrence in sub-surface waters of the Indonesian archipelago - Cordova, Muhammad Reza; Iskandar, Mochamad Riza; Surinati, Dewi; Kaisupy, Muhammad Taufik; Wibowo, Singgih Prasetyo Adi; Subandi, Riyana; Ulumuddin, Yaya Ihya; Purbonegoro, Triyoni; Yogaswara, Deny; Sani, Sofia Yuniar; Puspitasari, Rachma; Rositasari, Ricky; et al. (Frontiers in Marine Science, 2024)
The issue of plastic pollution in the marine environment is a matter of great concern. Our research presents pioneering findings on sub-surface microplastics in the Indonesian archipelagic waters. Data on microplastic presence in sub-surface water in the Indonesian Archipelagic Water is crucial for expanding our understanding of microplastic distribution from the surface to the bottom layers of the ocean, a research area that has been relatively overlooked. We discovered microplastic particles at 5 m depth below the surface through simultaneous pump method. The highest concentration of microplastics was discovered in Ambon, followed by North Java and North Sulawesi. In contrast, the lowest abundance of microplastics was detected in the Maluku Sea. These findings are consistent with prior studies establishing a relationship between human activity–as indicated by population density–-and microplastic pollution. However, our results indicate that levels of microplastics in Ambon were significantly higher than those found in other sampled areas, particularly compared to North Java, which boasts the highest population density in Indonesia. This disparity is likely due to a faster seawater flushing rate and shorter water residence time in North Java relative to Ambon. The origins and pathways through which these microplastics are introduced into Indonesian archipelagic waters remain uncertain. Based on particle composition (52.73% fibers and 51.38% size <500 µm), it appears that they may result from either larger plastic items being broken down during transportation over long distances by prevailing currents from input from coastal areas or as a byproduct of local activities. Additional research is necessary to gain a comprehensive understanding of microplastic in water columns. This includes investigating the fate of microplastics and examining their impact on marine organisms within this treasured ecosystem. Moreover, it is important to develop methods for mapping the worldwide distribution of microplastics.